MultiDarkLens Simulations: weak lensing light-cones and data base presentation. Issue 1 (8th June 2016) - Giocoli, Carlo; Jullo, Eric; Metcalf, R. Benton; de la Torre, Sylvain; Yepes, Gustavo; Prada, Francisco; Comparat, Johan; Göttlober, Stefan; Kyplin, Anatoly; Kneib, Jean-Paul; Petkova, Margarita; Shan, HuanYuan; et al.
Abstract: In this paper we present a large data base of weak lensing light cones constructed using different snapshots from the Big MultiDark simulation (BigMDPL). The ray-tracing through different multiple plane has been performed with the glamer code accounting both for single source redshifts and for sources distributed along the cosmic time. This first paper presents weak lensing forecasts and results according to the geometry of the VIPERS-W1 and VIPERS-W4 field of view. Additional fields will be available on our data base and new ones can be run upon request. Our data base also contains some tools for lensing analysis. In this paper we present results for convergence power spectra, one point and high order weak lensing statistics useful for forecasts and for cosmological studies. Covariance matrices have also been computed for the different realizations of the W1 and W4 fields. In addition we compute also galaxy-shear and projected density contrasts for different halo masses at two lens redshift according to the CFHTLS source redshift distribution both using stacking and cross-correlation techniques, finding very good agreement.